1998
DOI: 10.2307/3857431
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical Context in Organizations: Influences on Employee Attitudes and Behaviors

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 169.230.243.252 on Sun, Abstract: This field survey focused on two constructs that have been developed to represent the ethical context in organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
564
1
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 861 publications
(630 citation statements)
references
References 32 publications
16
564
1
12
Order By: Relevance
“…These findings are consistent with those of previous researchers who found that the correlation between EC and OC was positive and significant (Hunt et al, 1989;Kelley & Dorsch, 1991;Verbeke et al, 1996;Trevino et al, 1998;Singhapakdi et al, 1999;Babin et al, 2000;Schwepker, 2001;Oz, 2001;Valentine et al, 2002;Cullen et al, 2003;Vitell & Hidalgo, 2006;Tsui & Huang, 2008;Shafer, 2009;Zehir et al, 2011;Purhanudin et al, 2012).…”
Section: 00supporting
confidence: 83%
“…These findings are consistent with those of previous researchers who found that the correlation between EC and OC was positive and significant (Hunt et al, 1989;Kelley & Dorsch, 1991;Verbeke et al, 1996;Trevino et al, 1998;Singhapakdi et al, 1999;Babin et al, 2000;Schwepker, 2001;Oz, 2001;Valentine et al, 2002;Cullen et al, 2003;Vitell & Hidalgo, 2006;Tsui & Huang, 2008;Shafer, 2009;Zehir et al, 2011;Purhanudin et al, 2012).…”
Section: 00supporting
confidence: 83%
“…The third research stream examines the way decision-making on ethical matters is conducted, with various models proposed on the subject, such as those by Ferrell et al (1989), Ferrell and Gresham (1985, Hunt and Vitell (1986;2006), Jones (1991), Trevino (1986), and Trevino et al (1998). Such models explain how individuals make ethical decisions, thus enabling stakeholders to adjust their decision-making processes accordingly (e.g., Burnaz et al, 2009;Singhapakdi et al, 2010).…”
Section: Previous Researchmentioning
confidence: 99%
“…(Swierczed&Onishi, 2003). Punishment can be defined as "a superior's application of a negative consequence or the removal of a positive consequence following an employee's undesirable behavior with the intention of decreasing the frequency of that behavior" (Trevino et al, 1998). The use of punishment often creates conflicts within the organization, which then leads to loss of trust and loyalty, loss of productivity, dissatisfaction and an increase in stress levels (Challagalla&Shervani, 1996); (Doby&Caplan, 1995).…”
Section: 4 Illnessmentioning
confidence: 99%